Polarizing film with pressure-sensitive adhesive layer and image display device
The polarizing film with an adhesive layer on both sides addresses thickness unevenness and yield reduction, ensuring effective UV protection and maintaining display quality in image display devices.
Patent Information
- Application Number
- JP2022168882
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-10-21
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2035-02-26
AI Technical Summary
Existing polarizing films in image display devices face issues with thickness unevenness and reduced yield due to the use of transparent adhesives with ultraviolet absorption functions, leading to inadequate UV protection and potential deterioration of optical components.
A polarizing film with an adhesive layer on both sides, featuring a transparent protective film with a transmittance of 6% or more at 380 nm and an adhesive layer with UV absorption function, ensuring sufficient UV-cutting even when thin, thereby preventing deterioration of optical components.
The solution provides effective UV protection, reduces production issues, and maintains display quality by preventing UV-induced deterioration of components like liquid crystal panels and organic EL elements.
Smart Images

Figure 0007610560000004 
Figure 0007610560000005 
Figure 0007610560000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a polarizing film with an adhesive layer for use in an image display device. The present invention also relates to an image display device using the polarizing film with an adhesive layer. Examples of image display devices include liquid crystal display devices, organic EL (electroluminescence) display devices, PDPs (plasma display panels), and electronic paper. [Background technology]
[0002] Due to the image formation method of liquid crystal display devices and organic EL display devices, for example, in liquid crystal display devices, it is essential to place polarizing elements on both sides of the liquid crystal cell, and polarizing films are generally attached to the liquid crystal display devices. In addition to polarizing films, various optical elements have come to be used in display panels such as liquid crystal panels and organic EL panels in order to improve the display quality of the displays.
[0003] The polarizing films used in these image display devices generally have a structure in which a polarizer is sandwiched between two protective films, and triacetyl cellulose (TAC) is widely used as the protective films.
[0004] In recent years, with the trend toward lighter and thinner image display devices, thinner components are being required for the image display devices, and thinner protective films for polarizing films are also being required. When the thickness of the protective film is thin, it becomes difficult to sufficiently block ultraviolet rays incident on the image display device, and this causes problems such as accelerating the deterioration of not only polarizers but also various optical components such as liquid crystal panels and organic EL elements used in image display devices due to ultraviolet rays.
[0005] To solve such problems, for example, a double-sided pressure-sensitive adhesive sheet for an image display device is known, which is disposed between a surface protection panel and a viewing side of a liquid crystal module in the image display device to integrate the two members, and has at least one ultraviolet absorbing layer, a light transmittance of 30% or less at a wavelength of 380 nm, and a visible light transmittance of 80% or more at wavelengths longer than 430 nm (see, for example, Patent Document 1), and a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer containing an acrylic polymer and a triazine-based ultraviolet absorber (see, for example, Patent Document 2). It is also known that in a pressure-sensitive adhesive optical film in which a pressure-sensitive adhesive layer is provided on one or both sides of the optical film, the pressure-sensitive adhesive layer can be given ultraviolet absorbing ability (see, for example, Patent Document 3). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2012-211305 A [Patent Document 2] JP 2013-75978 A [Patent Document 3] Patent No. 4208187 Summary of the Invention [Problem to be solved by the invention]
[0007] In recent years, as described in Patent Documents 1 to 3, it has become known to use a transparent adhesive having an ultraviolet absorbing function to bond various components used in an image display device. However, this method has problems such as uneven thickness, poor yield, and workability.
[0008] Therefore, the present invention aims to provide a polarizing film with a pressure-sensitive adhesive layer that can solve the problem of reduced yield and can provide a sufficient ultraviolet ray blocking function even when the polarizing film is thin. Another object of the present invention is to provide an image display device using the polarizing film with a pressure-sensitive adhesive layer. [Means for solving the problem]
[0009] Means of the Invention The present inventors have conducted extensive research to solve the above problems, and as a result have found the following polarizing film with a pressure-sensitive adhesive layer, thereby completing the present invention.
[0010] That is, the present invention provides a polarizing film with a pressure-sensitive adhesive layer, which is used on the viewing side of an image display unit in an image display device, The polarizing film with a pressure-sensitive adhesive layer has a polarizing film and pressure-sensitive adhesive layers on both sides of the polarizing film, The polarizing film has a polarizer and transparent protective films on both sides of the polarizer, The transparent protective film on the viewing side of the polarizer has a transmittance of 6% or more at a wavelength of 380 nm; and The present invention relates to a polarizing film with a pressure-sensitive adhesive layer, wherein the pressure-sensitive adhesive layer on the viewing side of the polarizing film has an ultraviolet absorbing function.
[0011] It is preferable that the transparent protective film on the viewing side of the polarizer is at least one film selected from the group consisting of triacetyl cellulose film, acrylic film, polyethylene terephthalate film, and polyolefin film having a cyclo- or norbornene structure, and has a thickness of 40 μm or less.
[0012] The thickness of the pressure-sensitive adhesive layer on the viewing side of the polarizing film is preferably at least twice as thick as the thickness of the pressure-sensitive adhesive layer on the image display portion side of the polarizing film.
[0013] It is preferable that the pressure-sensitive adhesive layer on the viewing side of the polarizing film has a transmittance of 40% or less at a wavelength of 380 nm and a transmittance of 30% or more at a wavelength of 400 nm.
[0014] The pressure-sensitive adhesive layer on the viewing side of the polarizing film preferably has a b* value of 3.0 or less.
[0015] The pressure-sensitive adhesive layer on the viewing side of the polarizing film preferably contains an acrylic polymer as a base polymer.
[0016] The pressure-sensitive adhesive layer-attached polarizing film of the present invention is preferably used in a liquid crystal display device or an organic EL display device.
[0017] The present invention also relates to an image display device, characterized in that the above-mentioned pressure-sensitive adhesive layer-attached polarizing film is used on the viewing side of an image display section. Effect of the Invention
[0018] The polarizing film with a pressure-sensitive adhesive layer of the present invention has a structure in which a pressure-sensitive adhesive layer having an ultraviolet absorbing function is laminated in advance on the viewing side of the polarizing film, and therefore the problems of process elimination and yield reduction can be solved, and even if the polarizing film is thin, a sufficient ultraviolet blocking function can be imparted. In addition, the image display device of the present invention uses the polarizing film with a pressure-sensitive adhesive layer, and therefore can suppress deterioration of various optical members, including liquid crystal panels and organic EL elements, used in the image display device, due to ultraviolet rays. [Brief description of the drawings]
[0019] [Figure 1] 1 is a cross-sectional view that illustrates a schematic diagram of one embodiment of a pressure-sensitive adhesive layer-attached polarizing film of the present invention. [Diagram 2] 1 is a cross-sectional view that illustrates a schematic diagram of an embodiment of an image display device of the present invention. [Diagram 3] 1 is a cross-sectional view that illustrates a schematic diagram of an embodiment of an image display device of the present invention. [Figure 4] 1 is a cross-sectional view that illustrates a schematic diagram of an embodiment of an image display device of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] 1. Polarizing film with adhesive layer The pressure-sensitive adhesive layer-attached polarizing film of the present invention is used on the viewing side of an image display unit in an image display device, The polarizing film with a pressure-sensitive adhesive layer has a polarizing film and pressure-sensitive adhesive layers on both sides of the polarizing film, The polarizing film has a polarizer and transparent protective films on both sides of the polarizer, The transparent protective film on the viewing side of the polarizer has a transmittance of 6% or more at a wavelength of 380 nm; and The pressure-sensitive adhesive layer on the viewing side of the polarizing film has an ultraviolet absorbing function.
[0021] As shown in FIG. 1, the polarizing film 1 with the adhesive layer of the present invention may be configured to include a visible-side adhesive layer 2a / a visible-side transparent protective film 3a / a polarizer 4 / a transparent protective film 3b on the image display unit side / a pressure-sensitive adhesive layer 2b, and may further include a retardation film or the like. Specifically, the polarizing film 5 may be configured to include a visible-side adhesive layer 2a / a visible-side transparent protective film 3a / a polarizer 4 / a transparent protective film 3b on the image display unit side / a pressure-sensitive adhesive layer 2b on the image display unit side / a retardation film (not shown) / a pressure-sensitive adhesive layer (not shown) or the like. The polarizing film 5 is configured to include a visible-side transparent protective film 3a / a polarizer 4 / a transparent protective film 3b on the image display unit side. Each layer will be described in detail below.
[0022] (1) Visible side adhesive layer In the present invention, the pressure-sensitive adhesive layer on the viewing side of the polarizing film (viewing-side pressure-sensitive adhesive layer) has an ultraviolet ray absorbing function. The pressure-sensitive adhesive layer on the viewing side may have an ultraviolet ray absorbing function, and the composition thereof is not particularly limited.
[0023] The visible-side adhesive layer can be formed using an appropriate adhesive, and the type is not particularly limited. Examples of the adhesive include rubber-based adhesives, acrylic-based adhesives, silicone-based adhesives, urethane-based adhesives, vinyl alkyl ether-based adhesives, polyvinyl alcohol-based adhesives, polyvinylpyrrolidone-based adhesives, polyacrylamide-based adhesives, and cellulose-based adhesives. Among these adhesives, acrylic-based adhesives are preferably used because they have excellent optical transparency, appropriate adhesion, cohesion, and adhesive properties, and are excellent in weather resistance and heat resistance. The acrylic adhesive contains an acrylic polymer as a base polymer.
[0024] The visible-side adhesive layer using the acrylic adhesive is preferably formed by, for example, ultraviolet polymerization of an ultraviolet-curable acrylic adhesive composition containing a monomer component containing alkyl (meth)acrylate and / or a partial polymer of the monomer component, an ultraviolet absorber, and a photopolymerization initiator (A) having an absorption band at a wavelength of 400 nm or more. The adhesive layer formed by ultraviolet polymerization of the ultraviolet-curable acrylic adhesive composition can be formed to a thickness of 150 μm or more, and is therefore preferable because an adhesive layer of a wide range of thicknesses can be formed.
[0025] The alkyl (meth)acrylate may be, for example, one having a linear or branched alkyl group having 1 to 24 carbon atoms at the ester end. The alkyl (meth)acrylate may be used alone or in combination of two or more. The alkyl (meth)acrylate refers to alkyl acrylate and / or alkyl methacrylate, and (meth) in the present invention has the same meaning.
[0026] Examples of the alkyl (meth)acrylate include alkyl (meth)acrylates having a branch having 4 to 9 carbon atoms. The alkyl (meth)acrylates are preferred because they are easy to balance the adhesive properties. Specific examples include n-butyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, and isononyl (meth)acrylate, and these can be used alone or in combination of two or more.
[0027] In the present invention, the alkyl (meth)acrylate having an alkyl group having 1 to 24 carbon atoms at the ester terminal is preferably 40% by weight or more, more preferably 50% by weight or more, and even more preferably 60% by weight or more, of the total amount of monofunctional monomer components forming the (meth)acrylic polymer.
[0028] The monomer component may contain a copolymerizable monomer other than the alkyl (meth)acrylate as a monofunctional monomer component. The copolymerizable monomer may be used as the remainder of the alkyl (meth)acrylate in the monomer component.
[0029] The copolymerization monomer may include, for example, a cyclic nitrogen-containing monomer. As the cyclic nitrogen-containing monomer, a monomer having a polymerizable functional group with an unsaturated double bond such as a (meth)acryloyl group or a vinyl group and having a cyclic nitrogen structure may be used without any particular limitation. The cyclic nitrogen structure is preferably one having a nitrogen atom in the cyclic structure. Examples of the cyclic nitrogen-containing monomer include lactam vinyl monomers such as N-vinylpyrrolidone, N-vinyl-ε-caprolactam, and methylvinylpyrrolidone; vinyl monomers having a nitrogen-containing heterocycle such as vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, and vinylmorpholine. In addition, examples of the cyclic nitrogen-containing monomer include (meth)acrylic monomers containing a heterocycle such as a morpholine ring, a piperidine ring, a pyrrolidine ring, and a piperazine ring. Specific examples include N-acryloylmorpholine, N-acryloylpiperidine, N-methacryloylpiperidine, and N-acryloylpyrrolidine. Among the above cyclic nitrogen-containing monomers, lactam vinyl monomers are preferred.
[0030] In the present invention, the amount of the cyclic nitrogen-containing monomer is preferably 0.5 to 50% by weight, more preferably 0.5 to 40% by weight, and even more preferably 0.5 to 30% by weight, based on the total amount of monofunctional monomer components forming the (meth)acrylic polymer.
[0031] The monomer component used in the present invention may contain a hydroxyl group-containing monomer as a monofunctional monomer component. As the hydroxyl group-containing monomer, a monomer having a polymerizable functional group with an unsaturated double bond such as a (meth)acryloyl group or a vinyl group and having a hydroxyl group may be used without any particular limitation. As the hydroxyl group-containing monomer, for example, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate; and hydroxyalkyl cycloalkane (meth)acrylates such as (4-hydroxymethylcyclohexyl)methyl (meth)acrylate may be mentioned. Other examples include hydroxyethyl (meth)acrylamide, allyl alcohol, 2-hydroxyethyl vinyl ether, 4-hydroxybutyl vinyl ether, diethylene glycol monovinyl ether, etc. These can be used alone or in combination. Among these, hydroxyalkyl (meth)acrylates are preferred.
[0032] In the present invention, the hydroxyl group-containing monomer is preferably 1% by weight or more, more preferably 2% by weight or more, and even more preferably 3% by weight or more, based on the total amount of the monofunctional monomer components forming the (meth)acrylic polymer, from the viewpoint of increasing adhesive strength and cohesive strength. On the other hand, if the amount of the hydroxyl group-containing monomer is too much, the adhesive layer may become hard and adhesive strength may decrease, and the adhesive may become too viscous or gel, so the hydroxyl group-containing monomer is preferably 30% by weight or less, more preferably 27% by weight or less, and even more preferably 25% by weight or less, based on the total amount of the monofunctional monomer components forming the (meth)acrylic polymer.
[0033] Furthermore, the monomer component forming the (meth)acrylic polymer may contain other functional group-containing monomers as monofunctional monomers, such as carboxyl group-containing monomers and monomers having a cyclic ether group.
[0034] The carboxyl group-containing monomer may be any monomer having a polymerizable functional group with an unsaturated double bond, such as a (meth)acryloyl group or a vinyl group, and having a carboxyl group, without any particular limitations. Examples of the carboxyl group-containing monomer include (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, etc., which may be used alone or in combination. Anhydrides of itaconic acid and maleic acid may be used. Among these, acrylic acid and methacrylic acid are preferred, and acrylic acid is particularly preferred. In addition, a carboxyl group-containing monomer may be used as the monomer component used in the production of the (meth)acrylic polymer of the present invention, and on the other hand, a carboxyl group-containing monomer may not be used.
[0035] As the monomer having a cyclic ether group, those having a polymerizable functional group having an unsaturated double bond such as a (meth)acryloyl group or a vinyl group, and having a cyclic ether group such as an epoxy group or an oxetane group, can be used without any particular limitation. As the epoxy group-containing monomer, for example, glycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, etc. are mentioned. As the oxetane group-containing monomer, for example, 3-oxetanylmethyl (meth)acrylate, 3-methyl-oxetanylmethyl (meth)acrylate, 3-ethyl-oxetanylmethyl (meth)acrylate, 3-butyl-oxetanylmethyl (meth)acrylate, 3-hexyl-oxetanylmethyl (meth)acrylate, etc. are mentioned. These can be used alone or in combination.
[0036] In the present invention, the amount of the carboxyl group-containing monomer and the monomer having a cyclic ether group is preferably 30% by weight or less, more preferably 27% by weight or less, and even more preferably 25% by weight or less, of the total amount of monofunctional monomer components forming the (meth)acrylic polymer.
[0037] The monomer components forming the (meth)acrylic polymer of the present invention include, for example, copolymerizable monomers such as CH2=C(R 1 )COOR 2 (The above R 1 is hydrogen or a methyl group, R 2 represents a substituted alkyl group having 1 to 3 carbon atoms, or a cyclic cycloalkyl group.
[0038] Here, R 2 As the substituent of the substituted alkyl group having 1 to 3 carbon atoms as mentioned above, an aryl group having 3 to 8 carbon atoms or an aryloxy group having 3 to 8 carbon atoms is preferable. The aryl group is not limited, but a phenyl group is preferable.
[0039] Such CH2=C(R 1 )COOR 2 Examples of the monomer represented by the formula (I) include phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, cyclohexyl (meth)acrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate, etc. These can be used alone or in combination.
[0040] In the present invention, the CH2=C(R 1 )COOR 2 The (meth)acrylate represented by the formula (I) can be used in an amount of 50% by weight or less, preferably 45% by weight or less, more preferably 40% by weight or less, and even more preferably 35% by weight or less, based on the total amount of monofunctional monomer components forming the (meth)acrylic polymer.
[0041] Other copolymerizable monomers include vinyl acetate, vinyl propionate, styrene, α-methylstyrene; glycol-based acrylic ester monomers such as polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate; acrylic ester monomers such as tetrahydrofurfuryl (meth)acrylate, fluorine (meth)acrylate, silicone (meth)acrylate, and 2-methoxyethyl acrylate; amide group-containing monomers, amino group-containing monomers, imide group-containing monomers, N-acryloylmorpholine, and vinyl ether monomers. Also, monomers having a cyclic structure such as terpene (meth)acrylate and dicyclopentanyl (meth)acrylate can be used as copolymerizable monomers.
[0042] Further, examples of the silane monomers include those containing silicon atoms. Examples of the silane monomers include 3-acryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 4-vinylbutyltrimethoxysilane, 4-vinylbutyltriethoxysilane, 8-vinyloctyltrimethoxysilane, 8-vinyloctyltriethoxysilane, 10-methacryloyloxydecyltrimethoxysilane, 10-acryloyloxydecyltrimethoxysilane, 10-methacryloyloxydecyltriethoxysilane, and 10-acryloyloxydecyltriethoxysilane.
[0043] The monomer components forming the (meth)acrylic polymer of the present invention may contain, in addition to the monofunctional monomers exemplified above, a polyfunctional monomer, if necessary, in order to adjust the cohesive strength of the pressure-sensitive adhesive.
[0044] The polyfunctional monomer is a monomer having at least two polymerizable functional groups having an unsaturated double bond, such as a (meth)acryloyl group or a vinyl group, and examples thereof include (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and 1,2-ethylene glycol di(meth)acrylate. Examples of the polyhydric alcohols include ester compounds of polyhydric alcohols and (meth)acrylic acid, such as 1,6-hexanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and tetramethylolmethane tri(meth)acrylate; allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, urethane acrylate, butyl di(meth)acrylate, and hexyl di(meth)acrylate. Among these, trimethylolpropane tri(meth)acrylate, hexanediol di(meth)acrylate, and dipentaerythritol hexa(meth)acrylate can be preferably used. The polyfunctional monomers can be used alone or in combination of two or more.
[0045] The amount of polyfunctional monomer used varies depending on its molecular weight, the number of functional groups, etc., but is preferably 3 parts by weight or less, more preferably 2 parts by weight or less, and even more preferably 1 part by weight or less, based on 100 parts by weight of the total of monofunctional monomers. The lower limit is not particularly limited, but is preferably 0 parts by weight or more, and more preferably 0.001 parts by weight or more. By keeping the amount of polyfunctional monomer used within the above range, the adhesive strength can be improved.
[0046] In the present invention, the polymer may be a partial polymer of the monomer components.
[0047] The ultraviolet absorbing agent contained in the ultraviolet curing acrylic adhesive composition is not particularly limited, but examples thereof include triazine ultraviolet absorbing agents, benzotriazole ultraviolet absorbing agents, benzophenone ultraviolet absorbing agents, oxybenzophenone ultraviolet absorbing agents, salicylic acid ester ultraviolet absorbing agents, cyanoacrylate ultraviolet absorbing agents, etc., and these can be used alone or in combination of two or more. Among these, triazine ultraviolet absorbing agents and benzotriazole ultraviolet absorbing agents are preferred, and at least one ultraviolet absorbing agent selected from the group consisting of triazine ultraviolet absorbing agents having two or less hydroxyl groups in one molecule and benzotriazole ultraviolet absorbing agents having one benzotriazole skeleton in one molecule is preferred because it has good solubility in the monomer used to form the ultraviolet curing acrylic adhesive composition and has high ultraviolet absorbing ability at a wavelength of around 380 nm.
[0048] Specific examples of triazine-based ultraviolet absorbers having two or less hydroxyl groups in one molecule include 2,4-bis-[{4-(4-ethylhexyloxy)-4-hydroxy}-phenyl]-6-(4-methoxyphenyl)-1,3,5-triazine (Tinosorb S, manufactured by BASF), 2,4-bis[2-hydroxy-4-butoxyphenyl]-6-(2,4-dibutoxyphenyl)-1,3,5-triazine (TINUVIN 460, manufactured by BASF), 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl)-5-hydroxyphenyl and [(C10-C16 (mainly C12-C13) alkyloxy)methyl]oxirane reaction products (TINUVIN400, manufactured by BASF), 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl]-5-[3-(dodecyloxy)-2-hydroxypropoxy]phenol), 2-(2,4-dihydroxyf Examples of such phenols include the reaction product of 2-(4,6-diphenyl-1,3,5-triazine and (2-ethylhexyl)-glycidic acid ester (TINUVIN 405, manufactured by BASF), 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[(hexyl)oxy]-phenol (TINUVIN 1577, manufactured by BASF), 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]-phenol (ADK STAB LA46, manufactured by ADEKA), and 2-(2-hydroxy-4-[1-octyloxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine (TINUVIN 479, manufactured by BASF).
[0049] Benzotriazole-based UV absorbers having one benzotriazole skeleton per molecule include 2-(2H-benzotriazole-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol (TINUVIN 928, manufactured by BASF), 2-(2-hydroxy-5-tert-butylphenyl)-2H-benzotriazole (TINUVIN PS, manufactured by BASF), ester compound of benzenepropanoic acid and 3-(2H-benzotriazole-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy (C7-9 side chain and linear alkyl) (TINUVIN 384-2, manufactured by BASF), 2-(2H-benzotriazole-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (TINUVIN 900, manufactured by BASF), 2-(2H-benzotriazole-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (TINUVIN 900, manufactured by BASF), and 2-(2H-benzotriazole-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (TINUVIN 900, manufactured by BASF). methyl-3-(3-(2H-benzotriazol-2-yl)-5-t-butyl-4-hydroxyphenyl)propionate / polyethylene glycol 300 reaction product (TINUVIN 1130, BASF), 2-(2H-benzotriazol-2-yl)-p-cresol (TINUVIN P, manufactured by BASF), 2(2H-benzotriazol-2-yl)-4-6-bis(1-methyl-1-phenylethyl)phenol (TINUVIN234, manufactured by BASF), 2-[5-chloro(2H)-benzotriazol-2-yl]-4-methyl-6-(tert-butyl)phenol (TINUVIN326, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4,6-di-tert-pentylphenol (TINUVIN328, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4-(1,1,3,Examples of the 2-hydroxy-3-(3,4,5,6-tetrahydrophthalimido-methyl)-4-hydroxyphenyl)phenol include 3-(tetramethylbutyl)phenol (TINUVIN 329, manufactured by BASF), a reaction product of methyl 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl)propionate and polyethylene glycol 300 (TINUVIN 213, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-6-dodecyl-4-methylphenol (TINUVIN 571, manufactured by BASF), and 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimido-methyl)-5-methylphenyl]benzotriazole (Sumisorb 250, manufactured by Sumitomo Chemical Co., Ltd.).
[0050] Furthermore, examples of the benzophenone-based ultraviolet absorbers (benzophenone-based compounds) and oxybenzophenone-based ultraviolet absorbers (oxybenzophenone-based compounds) include 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid (anhydrous and trihydrate), 2-hydroxy-4-octyloxybenzophenone, 4-dodecyloxy-2-hydroxybenzophenone, 4-benzyloxy-2-hydroxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, and 2,2'-dihydroxy-4,4-dimethoxybenzophenone.
[0051] Examples of the salicylic acid ester-based ultraviolet absorbers (salicylic acid ester-based compounds) include phenyl-2-acryloyloxybenzoate, phenyl-2-acryloyloxy-3-methylbenzoate, phenyl-2-acryloyloxy-4-methylbenzoate, phenyl-2-acryloyloxy-5-methylbenzoate, phenyl-2-acryloyloxy-3-methoxybenzoate, phenyl-2-hydroxybenzoate, phenyl-2-hydroxy-3-methylbenzoate, phenyl-2-hydroxy-4-methylbenzoate, phenyl-2-hydroxy-5-methylbenzoate, phenyl-2-hydroxy-3-methoxybenzoate, and 2,4-di-tert-butylphenyl-3,5-di-tert-butyl-4-hydroxybenzoate (TINUVIN120, manufactured by BASF).
[0052] Examples of the cyanoacrylate-based ultraviolet absorber (cyanoacrylate-based compound) include alkyl-2-cyanoacrylate, cycloalkyl-2-cyanoacrylate, alkoxyalkyl-2-cyanoacrylate, alkenyl-2-cyanoacrylate, and alkynyl-2-cyanoacrylate.
[0053] The ultraviolet absorbent may be used alone or in combination of two or more kinds, but the total content is preferably about 0.1 to 5 parts by weight, more preferably about 0.5 to 3 parts by weight, based on 100 parts by weight of the monofunctional monomer component forming the (meth)acrylic polymer. By setting the amount of the ultraviolet absorbent added within the above range, the ultraviolet absorbing function of the pressure-sensitive adhesive layer can be fully exhibited and ultraviolet polymerization is not hindered, which is preferable.
[0054] The ultraviolet-curable acrylic adhesive composition used in the present invention preferably contains a photopolymerization initiator (A) having an absorption band at a wavelength of 400 nm or more. When the adhesive composition contains an ultraviolet absorber, ultraviolet light is absorbed by the ultraviolet absorber when ultraviolet polymerization is performed, and the composition cannot be sufficiently polymerized. However, the ultraviolet-curable acrylic adhesive composition used in the present invention contains a photopolymerization initiator (A) having an absorption band at a wavelength of 400 nm or more, and therefore can be sufficiently polymerized despite the inclusion of an ultraviolet absorber.
[0055] Examples of the photopolymerization initiator (A) having an absorption band at a wavelength of 400 nm or more include bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (Irgacure 819, manufactured by BASF) and 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide (LUCIRIN TPO, manufactured by BASF).
[0056] The photopolymerization initiator (A) having an absorption band at a wavelength of 400 nm or more may be used alone or in combination of two or more kinds.
[0057] The amount of the photopolymerization initiator (A) having an absorption band at a wavelength of 400 nm or more is not particularly limited, but is preferably less than the amount of the ultraviolet absorber, and is preferably about 0.005 to 1 part by weight, more preferably about 0.02 to 0.5 parts by weight, relative to 100 parts by weight of the monofunctional monomer component forming the (meth)acrylic polymer. By setting the amount of the photopolymerization initiator (A) within the above range, ultraviolet polymerization can be sufficiently promoted, which is preferable.
[0058] The ultraviolet-curable acrylic adhesive composition used in the present invention may contain a photopolymerization initiator (B) having an absorption band at a wavelength of less than 400 nm. The photopolymerization initiator (B) preferably does not have an absorption band at a wavelength of 400 nm or more. The photopolymerization initiator (B) is not particularly limited as long as it generates radicals by ultraviolet light and initiates photopolymerization and has an absorption band at a wavelength of less than 400 nm, and any photopolymerization initiator that is commonly used can be suitably used. For example, benzoin ether-based photopolymerization initiators, acetophenone-based photopolymerization initiators, α-ketol-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzyl-based photopolymerization initiators, benzophenone-based photopolymerization initiators, ketal-based photopolymerization initiators, thioxanthone-based photopolymerization initiators, acylphosphine oxide-based photopolymerization initiators, etc. may be used.
[0059] Specifically, examples of the benzoin ether-based photopolymerization initiator include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethan-1-one, and anisole methyl ether.
[0060] Examples of the acetophenone-based photopolymerization initiator include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone, and 4-t-butyldichloroacetophenone.
[0061] Examples of the α-ketol photopolymerization initiator include 2-methyl-2-hydroxypropiophenone, 1-[4-(2-hydroxyethyl)phenyl]-2-hydroxy-2-methylpropan-1-one, and the like.
[0062] An example of the photoactive oxime-based photopolymerization initiator is 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime.
[0063] An example of the benzoin-based photopolymerization initiator is benzoin.
[0064] The benzyl-based photopolymerization initiator includes, for example, benzyl.
[0065] Benzophenone-based photopolymerization initiators include, for example, benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexyl phenyl ketone, and the like.
[0066] Ketal-based photopolymerization initiators include benzyl dimethyl ketal and the like.
[0067] Examples of thioxanthone-based photopolymerization initiators include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.
[0068] Examples of the acylphosphine oxide photopolymerization initiator include 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and the like.
[0069] The photopolymerization initiator (B) having an absorption band at a wavelength of less than 400 nm can be used alone or in combination of two or more kinds. The photopolymerization initiator (B) having an absorption band at a wavelength of less than 400 nm can be added within a range that does not impair the effects of the present invention, and the amount added is preferably about 0.005 to 0.5 parts by weight, more preferably about 0.02 to 0.1 parts by weight, relative to 100 parts by weight of the monofunctional monomer component forming the (meth)acrylic polymer.
[0070] In the present invention, a photopolymerization initiator (B) having an absorption band at a wavelength of less than 400 nm is added to the monomer component, and the monomer component is partially polymerized by irradiating it with ultraviolet light. It is preferable to add the photopolymerization initiator (A) having an absorption band at a wavelength of 400 nm or more and the ultraviolet absorber to the (prepolymer composition) and carry out ultraviolet polymerization. When adding the photopolymerization initiator (A) having an absorption band at a wavelength of 400 nm or more to the partially polymerized monomer component (prepolymer composition) partially polymerized by ultraviolet irradiation, it is preferable to add the photopolymerization initiator after dissolving it in the monomer.
[0071] Furthermore, the ultraviolet-curable acrylic pressure-sensitive adhesive composition used in the present invention may contain a silane coupling agent. The amount of the silane coupling agent is preferably 1 part by weight or less, more preferably 0.01 to 1 part by weight, and even more preferably 0.02 to 0.6 parts by weight, based on 100 parts by weight of the monofunctional monomer component forming the (meth)acrylic polymer.
[0072] Examples of the silane coupling agent include epoxy group-containing silane coupling agents such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; amino group-containing silane coupling agents such as 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, and N-phenyl-γ-aminopropyltrimethoxysilane; (meth)acrylic group-containing silane coupling agents such as 3-acryloxypropyltrimethoxysilane and 3-methacryloxypropyltriethoxysilane; and isocyanate group-containing silane coupling agents such as 3-isocyanatepropyltriethoxysilane.
[0073] The ultraviolet-curable acrylic adhesive composition used in the present invention may contain a crosslinking agent. Examples of the crosslinking agent include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, silicone-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, silane-based crosslinking agents, alkyl etherified melamine-based crosslinking agents, metal chelate-based crosslinking agents, and peroxide-based crosslinking agents. The crosslinking agent may be used alone or in combination of two or more. Among these, isocyanate-based crosslinking agents are preferably used.
[0074] The above crosslinking agents may be used alone or in combination of two or more. The total content is preferably 5 parts by weight or less, more preferably 0.01 to 5 parts by weight, even more preferably 0.01 to 4 parts by weight, and particularly preferably 0.02 to 3 parts by weight, relative to 100 parts by weight of the monofunctional monomer component forming the (meth)acrylic polymer.
[0075] An isocyanate crosslinking agent refers to a compound having two or more isocyanate groups (including isocyanate regenerating functional groups in which the isocyanate groups are temporarily protected by a blocking agent or oligomerization, etc.) in one molecule. Examples of the isocyanate crosslinking agent include aromatic isocyanates such as tolylene diisocyanate and xylylene diisocyanate, alicyclic isocyanates such as isophorone diisocyanate, and aliphatic isocyanates such as hexamethylene diisocyanate.
[0076] More specifically, for example, lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate, alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate and isophorone diisocyanate, aromatic diisocyanates such as 2,4-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, xylylene diisocyanate and polymethylene polyphenyl isocyanate, trimethylolpropane / tolylene diisocyanate trimer adduct (product name: Coronate L, manufactured by Nippon Polyurethane Industry Co., Ltd.), trimethylolpropane / hexamethylene diisocyanate trimer adduct (product name: Examples of such polyisocyanates include isocyanate adducts such as Coronate HL, manufactured by Nippon Polyurethane Industry Co., Ltd., and an isocyanurate of hexamethylene diisocyanate (trade name: Coronate HX, manufactured by Nippon Polyurethane Industry Co., Ltd.), a trimethylolpropane adduct of xylylene diisocyanate (trade name: D110N, manufactured by Mitsui Chemicals, Inc.), and a trimethylolpropane adduct of hexamethylene diisocyanate (trade name: D160N, manufactured by Mitsui Chemicals, Inc.); polyether polyisocyanates, polyester polyisocyanates, and adducts of these with various polyols, and polyisocyanates that have been multifunctionalized with an isocyanurate bond, a biuret bond, an allophanate bond, or the like.
[0077] The ultraviolet-curable acrylic adhesive composition used in the present invention may contain appropriate additives in addition to the above-mentioned components depending on the application, such as tackifiers (e.g., rosin derivative resins, polyterpene resins, petroleum resins, oil-soluble phenolic resins, etc., which are solid, semi-solid, or liquid at room temperature); fillers such as hollow glass balloons; plasticizers; antioxidants; antioxidants; and the like.
[0078] In the present invention, the ultraviolet-curable acrylic adhesive composition is preferably adjusted to a viscosity suitable for application on a substrate. The viscosity of the ultraviolet-curable acrylic adhesive composition is adjusted, for example, by adding various polymers such as thickening additives, polyfunctional monomers, etc., or by partially polymerizing the monomer components in the ultraviolet-curable acrylic adhesive composition. The partial polymerization may be performed before or after adding various polymers such as thickening additives, polyfunctional monomers, etc. The viscosity of the ultraviolet-curable acrylic adhesive composition varies depending on the amount of additives, etc., so the polymerization rate when the monomer components in the ultraviolet-curable acrylic adhesive composition are partially polymerized cannot be uniquely determined, but as a guideline, it is preferably about 20% or less, more preferably about 3 to 20%, and even more preferably about 5 to 15%. If it exceeds 20%, the viscosity becomes too high, making it difficult to apply to a substrate.
[0079] The visible-side pressure-sensitive adhesive layer can be formed by applying the ultraviolet-curable acrylic pressure-sensitive adhesive composition to at least one surface of a substrate and irradiating the ultraviolet-curable acrylic pressure-sensitive adhesive composition with ultraviolet light.
[0080] The substrate is not particularly limited, and for example, various substrates such as a release film, a transparent resin film substrate, and a polarizing film described later can be suitably used as the substrate. When the visible-side pressure-sensitive adhesive layer is formed on a substrate other than a polarizing film, the visible-side pressure-sensitive adhesive layer can be transferred by being attached to the polarizing film.
[0081] Examples of the material constituting the release film include resin films such as polyethylene, polypropylene, polyethylene terephthalate, and polyester films; porous materials such as paper, cloth, and nonwoven fabrics; nets, foam sheets, metal foils, and appropriate thin sheets such as laminates thereof. Among these, resin films are preferably used because of their excellent surface smoothness.
[0082] Examples of the resin film include polyethylene film, polypropylene film, polybutene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyethylene terephthalate film, polybutylene terephthalate film, polyurethane film, and ethylene-vinyl acetate copolymer film.
[0083] The thickness of the release film is usually 5 to 200 μm, and preferably about 5 to 100 μm. The release film may be subjected to a release and antifouling treatment using a silicone-based, fluorine-based, long-chain alkyl-based or fatty acid amide-based release agent, silica powder, or the like, or an antistatic treatment such as a coating type, kneading type, or deposition type. In particular, by appropriately performing a release treatment such as a silicone treatment, a long-chain alkyl treatment, or a fluorine treatment on the surface of the release film, the releasability from the pressure-sensitive adhesive layer can be further improved.
[0084] The transparent resin film substrate is not particularly limited, and various resin films having transparency are used. The resin film is formed of a single layer film. For example, the material thereof may be polyester-based resins such as polyethylene terephthalate and polyethylene naphthalate, acetate-based resins, polyethersulfone-based resins, polycarbonate-based resins, polyamide-based resins, polyimide-based resins, polyolefin-based resins, (meth)acrylic-based resins, polyvinyl chloride-based resins, polyvinylidene chloride-based resins, polystyrene-based resins, polyvinyl alcohol-based resins, polyarylate-based resins, polyphenylene sulfide-based resins, etc. Among these, polyester-based resins, polyimide-based resins, and polyethersulfone-based resins are particularly preferred.
[0085] The thickness of the film substrate is preferably from 15 to 200 μm, and more preferably from 25 to 188 μm.
[0086] The method for applying the ultraviolet-curable acrylic pressure-sensitive adhesive composition onto the substrate is not particularly limited, and any suitable known method can be used, such as roll coating, kiss roll coating, gravure coating, reverse coating, roll brushing, spray coating, dip roll coating, bar coating, knife coating, air knife coating, curtain coating, lip coating, or die coating.
[0087] The illuminance of the ultraviolet light irradiated to the ultraviolet-curable acrylic adhesive composition is 5 mW / cm 2 The illuminance of the ultraviolet light is preferably 5 mW / cm or more. 2 If the ultraviolet ray is less than 200 mW / cm2, the polymerization reaction time will be long, and the productivity may be poor. 2 The illuminance of the ultraviolet light is preferably 200 mW / cm or less. 2 If the dose exceeds 100 mJ / cm, the photopolymerization initiator is consumed rapidly, causing the polymer to have a low molecular weight and reducing its holding power, especially at high temperatures. 2 ~5000mJ / cm 2 It is preferable that:
[0088] The ultraviolet lamp used in the present invention is not particularly limited, but an LED lamp is preferable. Since an LED lamp emits less heat than other ultraviolet lamps, the temperature during polymerization of the adhesive layer can be suppressed. Therefore, it is possible to prevent the polymer from being depolymerized, prevent the cohesive strength of the adhesive layer from decreasing, and increase the holding power at high temperatures when the adhesive layer is made into an adhesive sheet. It is also possible to combine multiple ultraviolet lamps. It is also possible to irradiate ultraviolet rays intermittently, and provide a light period in which ultraviolet rays are irradiated and a dark period in which ultraviolet rays are not irradiated.
[0089] In the present invention, the final polymerization rate of the monomer components in the ultraviolet-curable acrylic pressure-sensitive adhesive composition is preferably 90% or more, more preferably 95% or more, and even more preferably 98% or more.
[0090] In the present invention, the peak wavelength of the ultraviolet light irradiated to the ultraviolet-curable acrylic pressure-sensitive adhesive composition is preferably within the range of 200 to 500 nm, more preferably within the range of 300 to 450 nm. If the peak wavelength of the ultraviolet light exceeds 500 nm, the photopolymerization initiator may not be decomposed, and the polymerization reaction may not start. If the peak wavelength of the ultraviolet light is less than 200 nm, the polymer chain may be cut, and the adhesive properties may be reduced.
[0091] Since the reaction is inhibited by oxygen in the air, it is preferable to form a release film or the like on the coating layer of the acrylic pressure-sensitive adhesive composition to block oxygen, or to carry out the photopolymerization reaction under a nitrogen atmosphere. Examples of the release film include those mentioned above. When a release film is used, the release film can be used as it is as a separator for the polarizing film with the pressure-sensitive adhesive layer.
[0092] From the viewpoint of ensuring ultraviolet absorbing function, the thickness of the viewer-side adhesive layer is preferably at least twice, more preferably at least five times, and even more preferably at least ten times, the thickness of the adhesive layer on the image display section side of the polarizing film described later (image display section side adhesive layer). Specifically, the thickness of the viewer-side adhesive layer is preferably at least 50 μm, more preferably at least 100 μm, and even more preferably at least 150 μm. The upper limit of the thickness of the viewer-side adhesive layer is not particularly limited, but is preferably 10 mm or less. If the thickness of the adhesive layer exceeds 10 mm, ultraviolet light transmission becomes difficult, polymerization of the monomer component takes a long time, and productivity may be poor, which is not preferable.
[0093] In addition, when the ultraviolet-curable acrylic pressure-sensitive adhesive composition used in the present invention contains a photopolymerization initiator (B), it is preferable to irradiate a composition containing a monomer component containing an alkyl (meth)acrylate and the photopolymerization initiator (B) (sometimes referred to as a "pre-added polymerization initiator") with ultraviolet light to form a partial polymer of the monomer component, and to add an ultraviolet absorber and a photopolymerization initiator (A) (sometimes referred to as a "post-added polymerization initiator") having an absorption band at a wavelength of 400 nm or more to the partial polymer of the monomer component to prepare an ultraviolet-curable acrylic pressure-sensitive adhesive composition. The polymerization rate of the partial polymer is preferably about 20% or less, more preferably about 3 to 20%, and even more preferably about 5 to 15%. The ultraviolet irradiation conditions are as described above.
[0094] As described above, when a pressure-sensitive adhesive layer is formed from an ultraviolet-curable acrylic pressure-sensitive adhesive composition containing a photopolymerization initiator (B), the polymerization rate of the monomer components can be increased by carrying out the polymerization in two steps as described above, and the ultraviolet absorbing function of the finally produced pressure-sensitive adhesive layer can be improved.
[0095] The gel fraction of the pressure-sensitive adhesive layer on the viewing side of the present invention is not particularly limited, but is preferably 50% or more, more preferably 75% or more, and even more preferably 85% or more. If the gel fraction of the pressure-sensitive adhesive layer on the viewing side is small, the cohesive strength may be poor, and if it is too large, the adhesive strength may be poor.
[0096] The transmission b* value of the viewing-side pressure-sensitive adhesive layer is not particularly limited, but is preferably 3.0 or less, more preferably 1.5 or less, and even more preferably 0.5 or less. The b* value refers to the b* value (chromaticity) in the L*a*b* color system in accordance with JIS Z8729, and can be measured, for example, using a spectrophotometer (product name: U4100, manufactured by Hitachi High-Technologies Corporation).
[0097] The transmittance of the viewing-side pressure-sensitive adhesive layer at a wavelength of 380 nm is preferably 40% or less, more preferably 20% or less, and even more preferably 8% or less. When the transmittance at a wavelength of 380 nm is in the above range, incident ultraviolet light can be sufficiently blocked, and deterioration of optical components such as liquid crystal panels, organic EL elements, polarizers, etc. can be suppressed.
[0098] The transmittance of the viewing-side pressure-sensitive adhesive layer at a wavelength of 400 nm is preferably 30% or more, more preferably 50% or more, and more preferably 70% or more. When the transmittance wavelength at a wavelength of 400 nm is in the above range, the incident visible light can be sufficiently transmitted, and sufficient visibility can be ensured in an image display device, which is preferable.
[0099] (2) Adhesive layer on the image display side The adhesive layer on the image display section side surface of the polarizing film (image display section side adhesive layer) is not particularly limited, and may be the same as the ultraviolet-curable acrylic adhesive composition described in detail for the viewing side adhesive layer, or any of various commonly used adhesive layers.
[0100] The adhesive layer on the image display unit side surface can be formed using an appropriate adhesive, and there is no particular restriction on the type. Examples of the adhesive include rubber-based adhesives, acrylic-based adhesives, silicone-based adhesives, urethane-based adhesives, vinyl alkyl ether-based adhesives, polyvinyl alcohol-based adhesives, polyvinyl pyrrolidone-based adhesives, polyacrylamide-based adhesives, and cellulose-based adhesives. Among these adhesives, acrylic-based adhesives are preferably used because they have excellent optical transparency, exhibit appropriate adhesive properties such as adhesion, cohesion, and adhesion, and are excellent in weather resistance and heat resistance.
[0101] The acrylic adhesive has an acrylic polymer having a monomer unit of (meth)acrylic acid alkyl ester as a main skeleton as a base polymer. The (meth)acrylic acid alkyl ester constituting the main skeleton of the acrylic polymer can be the same as that used in the ultraviolet-curable acrylic adhesive composition forming the visible-side adhesive layer. The copolymerization monomer and its ratio can also be the same as that used in the ultraviolet-curable acrylic adhesive composition.
[0102] The acrylic polymer can be produced by various known methods, and for example, radical polymerization methods such as bulk polymerization, solution polymerization, and suspension polymerization can be appropriately selected. As the radical polymerization initiator, various known azo-based and peroxide-based initiators can be used. The reaction temperature is usually about 50 to 80°C, and the reaction time is 1 to 8 hours. Among the above production methods, the solution polymerization method is preferable, and ethyl acetate, toluene, etc. are generally used as the solvent for the acrylic polymer. The solution concentration is usually about 20 to 80% by weight.
[0103] The pressure-sensitive adhesive may be a pressure-sensitive adhesive composition containing a crosslinking agent. Examples of the crosslinking agent include those mentioned above, but isocyanate-based crosslinking agents are particularly preferred. The blending ratio of the acrylic polymer and the crosslinking agent is not particularly limited, but in general, the crosslinking agent (solid content) is preferably about 0.001 to 20 parts by weight, more preferably about 0.01 to 15 parts by weight, per 100 parts by weight of the acrylic polymer (solid content).
[0104] Furthermore, the adhesive may contain, as necessary, tackifiers, plasticizers, fillers made of glass fibers, glass beads, metal powders, other inorganic powders, pigments, colorants, fillers, antioxidants, ultraviolet absorbers, silane coupling agents, etc., and may also contain various additives within the scope of the present invention.Also, the adhesive layer may contain fine particles and exhibit light diffusion properties.As the silane coupling agent, the above-mentioned ones may be mentioned.
[0105] The image display unit side pressure-sensitive adhesive layer is formed by applying the pressure-sensitive adhesive to various substrates such as a polarizing film or a release film, and drying the applied pressure-sensitive adhesive. When the pressure-sensitive adhesive layer is formed on various substrates such as a release film, the pressure-sensitive adhesive layer can be transferred by bonding to the polarizing film. The pressure-sensitive adhesive application method and the various substrates can be the same as those of the ultraviolet-curable acrylic pressure-sensitive adhesive composition and the various substrates.
[0106] In the coating step, the coating amount is controlled so that the formed adhesive layer has a predetermined thickness (thickness after drying). The thickness of the image display section side adhesive layer is not particularly limited, but is preferably 1 / 2 or less, more preferably 1 / 5 or less, and more preferably 1 / 10 or less of the thickness of the viewing side adhesive layer. Specifically, the thickness of the image display section side adhesive layer is preferably about 1 to 100 μm, more preferably about 3 to 50 μm, and even more preferably about 5 to 30 μm.
[0107] When forming the image display unit side pressure-sensitive adhesive layer, the applied pressure-sensitive adhesive is dried. The drying temperature and drying time are not particularly limited and may be appropriately set, but are preferably, for example, about 80 to 200° C. and 0.5 to 10 minutes.
[0108] When the pressure-sensitive adhesive layer on the image display section side is exposed, the pressure-sensitive adhesive layer may be protected with a release film until it is put to practical use. The release film can be used as it is as a separator for the pressure-sensitive adhesive layer-attached polarizing film, which can simplify the process.
[0109] (3) Polarizing film The polarizing film used in the present invention is characterized in that it has a polarizer and transparent protective films on both sides of the polarizer, and the transparent protective film on the viewing side of the polarizer (viewing-side transparent protective film) has a transmittance of 6% or more at a wavelength of 380 nm.
[0110] (3-1) Transparent protective film on the viewing side The transmittance of the visible-side transparent protective film used in the present invention at a wavelength of 380 nm is 6% or more, preferably 10% or more, and more preferably 15% or more. The upper limit of the transmittance at a wavelength of 380 nm is not particularly limited, but is preferably 90% or less, and more preferably 30% or less. When the transmittance of the visible-side transparent protective film at a wavelength of 380 nm is within the above range, it is possible to achieve a sufficient ultraviolet absorbing ability by combining the visible-side transparent protective film with a thin film and the visible-side pressure-sensitive adhesive layer (containing an ultraviolet absorbing agent). Even if the visible-side transparent protective film does not have an ultraviolet absorbing ability, the ultraviolet absorbing function can be fully compensated for by the ultraviolet absorption by the visible-side pressure-sensitive adhesive layer, so that the transmittance at a wavelength of 380 nm of 90% or less has a sufficient ultraviolet absorbing ability. In addition, when the visible-side pressure-sensitive adhesive layer has a transmittance at a wavelength of 380 nm of 40% or less, it is preferable from the viewpoint of ultraviolet absorbing ability that the transmittance of the visible-side transparent protective film at a wavelength of 380 nm is 30% or less.
[0111] The material for forming the visible-side transparent protective film is preferably one having excellent transparency, mechanical strength, thermal stability, moisture barrier properties, isotropy, etc. Examples of the material include polyester-based polymers such as polyethylene terephthalate and polyethylene naphthalate, cellulose-based polymers such as diacetyl cellulose and triacetyl cellulose, acrylic polymers such as polymethyl methacrylate, styrene-based polymers such as polystyrene and acrylonitrile-styrene copolymers (AS resins), polycarbonate-based polymers, etc. In addition, examples of the polymer for forming the transparent protective film include polyethylene, polypropylene, polyolefins having a cyclo- or norbornene structure, polyolefin-based polymers such as ethylene-propylene copolymers, vinyl chloride-based polymers, amide-based polymers such as nylon and aromatic polyamide, imide-based polymers, sulfone-based polymers, polyethersulfone-based polymers, polyetheretherketone-based polymers, polyphenylene sulfide-based polymers, vinyl alcohol-based polymers, vinylidene chloride-based polymers, vinyl butyral-based polymers, arylate-based polymers, polyoxymethylene-based polymers, epoxy-based polymers, and blends of the above polymers. The transparent protective film can also be formed as a cured layer of a thermosetting or ultraviolet curing resin such as an acrylic, urethane, acrylic urethane, epoxy, silicone, etc. Among these, the viewing-side transparent protective film is preferably at least one film selected from the group consisting of a triacetyl cellulose film, an acrylic film (a film using an acrylic polymer), a polyethylene terephthalate film, and a polyolefin film having a cyclo- or norbornene structure, and more preferably a triacetyl cellulose film.
[0112] The thickness of the viewer-side transparent protective film is not particularly limited, but is preferably 40 μm or less, more preferably 35 μm or less, and even more preferably 30 μm or less. The lower limit of the thickness of the viewer-side transparent protective film is not particularly limited, but is preferably 1 μm or more. When the thickness of the viewer-side transparent protective film is in the above range, it is preferable because the polarizing film can be sufficiently thinned and the protective function of the polarizer is not impaired.
[0113] The polarizer and the viewing-side protective film described below are preferably adhered to each other via a water-based adhesive or the like. Examples of the water-based adhesive include isocyanate-based adhesives, polyvinyl alcohol-based adhesives, gelatin-based adhesives, vinyl-based latex-based adhesives, water-based polyurethanes, water-based polyesters, and the like. In addition to the above, examples of the adhesive between the polarizer and the viewing-side transparent protective film include ultraviolet-curing adhesives and electron beam-curing adhesives. The electron beam-curing polarizing film adhesive shows suitable adhesion to the above-mentioned various viewing-side transparent protective films. The adhesive used in the present invention may contain a metal compound filler.
[0114] The surface of the viewer-side transparent protective film to which the polarizer is not attached may be provided with a hard coat layer, anti-reflection treatment, anti-sticking treatment, or treatment for diffusing or anti-glare.
[0115] (3-2) Polarizer The polarizer is not particularly limited, and various polarizers can be used. Examples of polarizers include hydrophilic polymer films such as polyvinyl alcohol films, partially formalized polyvinyl alcohol films, and partially saponified ethylene-vinyl acetate copolymer films, which are uniaxially stretched after adsorbing a dichroic substance such as iodine or a dichroic dye, and polyene-based oriented films such as dehydrated polyvinyl alcohol and dehydrochlorinated polyvinyl chloride. Among these, polarizers made of a polyvinyl alcohol film and a dichroic substance such as iodine are suitable. The thickness of these polarizers is not particularly limited, but is generally about 5 to 80 μm.
[0116] A polarizer obtained by dyeing a polyvinyl alcohol-based film with iodine and stretching it uniaxially can be produced, for example, by immersing polyvinyl alcohol in an aqueous solution of iodine to dye it and stretching it to 3 to 7 times its original length. If necessary, it can also be immersed in an aqueous solution of potassium iodide or the like which may contain boric acid, zinc sulfate, zinc chloride, or the like. Furthermore, if necessary, the polyvinyl alcohol-based film can be immersed in water and washed before dyeing. Washing the polyvinyl alcohol-based film with water can wash off dirt and blocking inhibitors on the surface of the polyvinyl alcohol-based film, and also has the effect of preventing unevenness such as uneven dyeing by swelling the polyvinyl alcohol-based film. Stretching may be performed after dyeing with iodine, or may be stretched while dyeing, or may be dyed with iodine after stretching. Stretching can be performed in an aqueous solution of boric acid, potassium iodide, or the like, or in a water bath.
[0117] In the present invention, a thin polarizer having a thickness of 10 μm or less can also be used. From the viewpoint of thinning, the thickness is preferably 1 to 7 μm. Such a thin polarizer has less thickness unevenness, excellent visibility, and excellent durability due to less dimensional change, and is also preferable in that the thickness of the polarizing film can be reduced.
[0118] Representative examples of the thin polarizer include the thin polarizing films described in JP-A-51-069644, JP-A-2000-338329, WO-A-2010 / 100917, WO-A-2010 / 100917, or Japanese Patent No. 4751481 and JP-A-2012-073563. These thin polarizing films can be obtained by a manufacturing method including a step of stretching a polyvinyl alcohol-based resin (hereinafter also referred to as PVA-based resin) layer and a resin substrate for stretching in a laminated state, and a step of dyeing. With this manufacturing method, even if the PVA-based resin layer is thin, it can be stretched without problems such as breakage due to stretching because it is supported by the resin substrate for stretching.
[0119] As the thin polarizing film, among the production methods including a step of stretching and a step of dyeing a laminate, those obtained by a production method including a step of stretching in an aqueous boric acid solution as described in WO 2010 / 100917, WO 2010 / 100917, Japanese Patent No. 4751481, and JP-A 2012-073563 are preferred, in that they can be stretched at a high ratio and have improved polarization performance, and in particular those obtained by a production method including a step of auxiliary in-air stretching before stretching in an aqueous boric acid solution as described in Japanese Patent No. 4751481 and JP-A 2012-073563 are preferred.
[0120] (3-3) Transparent protective film on the image display side The image display side transparent protective film may be any of those conventionally used. Specifically, a transparent protective film formed from a material having excellent transparency, mechanical strength, thermal stability, moisture blocking properties, isotropy, etc. is preferred, and examples thereof include polyester polymers such as polyethylene terephthalate and polyethylene naphthalate, cellulose polymers such as diacetyl cellulose and triacetyl cellulose, acrylic polymers such as polymethyl methacrylate, styrene polymers such as polystyrene and acrylonitrile-styrene copolymer (AS resin), polycarbonate polymers, etc. Examples of the polymer forming the transparent protective film include polyethylene, polypropylene, polyolefins having a cyclo- or norbornene structure, polyolefin-based polymers such as ethylene-propylene copolymers, vinyl chloride-based polymers, amide-based polymers such as nylon and aromatic polyamides, imide-based polymers, sulfone-based polymers, polyethersulfone-based polymers, polyetheretherketone-based polymers, polyphenylene sulfide-based polymers, vinyl alcohol-based polymers, vinylidene chloride-based polymers, vinyl butyral-based polymers, arylate-based polymers, polyoxymethylene-based polymers, epoxy-based polymers, and blends of the above polymers. The transparent protective film can also be formed as a cured layer of a thermosetting or ultraviolet-curing resin such as an acrylic, urethane, acrylic urethane, epoxy, or silicone.
[0121] The thickness of the image display unit side protective film can be appropriately determined, but is generally about 1 to 500 μm in terms of strength, workability such as handleability, thinness, and the like.
[0122] The polarizer and the transparent protective film on the image display section side are also usually adhered to each other via a water-based adhesive, etc. Examples of the water-based adhesive include those mentioned above.
[0123] The surface of the transparent protective film on the image display portion side to which the polarizer is not attached may be provided with a hard coat layer, anti-reflection treatment, anti-sticking treatment, or treatment for diffusion or anti-glare purposes.
[0124] 2. Image display device The image display device of the present invention is characterized by using the pressure-sensitive adhesive layer-attached polarizing film of the present invention.
[0125] As an example of a specific configuration of the image display device, for example, as shown in FIG. 2 to FIG. 4, a cover glass or cover plastic 6 / visual side adhesive layer 2a / visual side transparent protective film 3a / polarizer 4 / image display unit side transparent protective film 3b / image display unit side adhesive layer 2b / liquid crystal display device (LCD) or organic EL display device (OLED) 7 (FIG. 2); cover glass or cover plastic 6 / adhesive layer 8a / sensor layer 9 / visual side adhesive layer 2a / visual side transparent protective film 3a / polarizer 4 / image display unit side transparent protective film Examples of image displays in which the layers are laminated in this order include: cover glass or cover plastic 6 / adhesive layer 8a / sensor layer 9 / adhesive layer 8b / sensor layer 9 / visible-side adhesive layer 2a / visible-side transparent protective film 3a / polarizer 4 / image-display-part-side transparent protective film 3b / image-display-part-side adhesive layer 2b / liquid crystal display device (LCD) or organic electroluminescence display device (OLED) 7 (FIG. 3); cover glass or cover plastic 6 / adhesive layer 8a / sensor layer 9 / adhesive layer 8b / sensor layer 9 / visible-side adhesive layer 2a / visible-side transparent protective film 3a / polarizer 4 / image-display-part-side transparent protective film 3b / image-display-part-side adhesive layer 2b / liquid crystal display device (LCD) or organic electroluminescence display device (OLED) 7 (FIG. 4). The adhesive layer-attached polarizing film 1 of the present invention refers to the portion of "visible-side adhesive layer 2a / visible-side transparent protective film 3a / polarizer 4 / image-display-part-side transparent protective film 3b / image-display-part-side adhesive layer 2b" in the above-mentioned configuration, and may also include a retardation film and the like in addition to these. In addition, when a retardation film is included, specifically, a pressure-sensitive adhesive layer can be laminated between the image display unit side pressure-sensitive adhesive layer 2b and a liquid crystal display device (LCD) or an organic electroluminescence display device (OLED) 7. In addition, a pressure-sensitive adhesive layer and / or an adhesive layer can be appropriately used in laminating each layer.
[0126] Examples of image display devices include liquid crystal display devices, organic EL (electroluminescence) display devices, PDPs (plasma display panels), electronic paper, and the like. Among these, liquid crystal display devices and organic EL (electroluminescence) display devices having the above-mentioned configurations are preferred. EXAMPLES
[0127] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. In each example, parts and percentages are all based on weight. The evaluation items in the examples were measured as follows.
[0128] Production Example 1 (Production of Acrylic Pressure Sensitive Adhesive Composition (a-1)) 2-Ethylhexyl acrylate (2EHA) 78 parts by weight, N-vinyl-2-pyrrolidone A monomer mixture consisting of 18 parts by weight of NVP and 4 parts by weight of 2-hydroxyethyl acrylate (HEA) was mixed with 0.035 parts by weight of 1-hydroxycyclohexyl phenyl ketone (product name: Irgacure 184, having an absorption band at wavelengths of 200 to 370 nm, manufactured by BASF) and 0.035 parts by weight of 2,2-dimethoxy-1,2-diphenylethan-1-one (product name: Irgacure 651, having an absorption band at wavelengths of 200 to 380 nm, manufactured by BASF) as photopolymerization initiators, and then irradiated with ultraviolet light until the viscosity (measurement conditions: BH viscometer No. 5 rotor, 10 rpm, measurement temperature 30°C) reached approximately 20 Pa·s, to obtain a prepolymer composition (polymerization rate: 8%) in which a portion of the monomer components was polymerized. Next, 0.15 parts by weight of hexanediol diacrylate (HDDA) and 0.3 parts by weight of a silane coupling agent (product name: KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.) were added to the prepolymer composition and mixed to obtain an acrylic pressure-sensitive adhesive composition (a-1).
[0129] Production Example 2 (Production of acrylic pressure-sensitive adhesive composition (a-2)) 67 parts by weight of butyl acrylate (BA), 14 parts by weight of cyclohexyl acrylate (CHA), 27 parts by weight of 4-hydroxybutyl acrylate (4HBA), 0.05 parts by weight of 2,2-dimethoxy-1,2-diphenyl-1-one (product name: Irgacure 651, having an absorption band at a wavelength of 200 to 380 nm, manufactured by BASF Japan) as a photopolymerization initiator, and 0.05 parts by weight of 1-hydroxy-cyclohexyl-phenyl-ketone (product name: Irgacure 184, having an absorption band at a wavelength of 200 to 370 nm, manufactured by BASF Japan) were charged into a four-neck flask, and the mixture was exposed to ultraviolet light under a nitrogen atmosphere to cause partial photopolymerization, thereby obtaining a partially polymerized product (monomer syrup) with a polymerization rate of 10%. Next, 0.15 parts by weight of dipentaerythritol penta- and hexaacrylate (DPHA) and 0.3 parts by weight of a silane coupling agent (product name: KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.) were added to the partial polymerization product, mixed, and irradiated with ultraviolet light to obtain an acrylic pressure-sensitive adhesive composition (a-2).
[0130] Production Example 3 (Production of Pressure-Sensitive Adhesive Layer (B-1) on Image Display Side) Into a separable flask equipped with a thermometer, a stirrer, a reflux condenser, and a nitrogen gas inlet tube, 95 parts of butyl acrylate, 5 parts of acrylic acid, 0.2 parts of azobisisobutyronitrile as a polymerization initiator, and 233 parts of ethyl acetate were charged, and then nitrogen gas was introduced and the mixture was substituted with nitrogen for about 1 hour while stirring. The flask was then heated to 60°C and reacted for 7 hours to obtain an acrylic polymer with a weight average molecular weight (Mw) of 1.1 million. To the above acrylic polymer solution (solid content: 100 parts by weight), 0.8 parts by weight of trimethylolpropane tolylene diisocyanate (product name: Coronate L, manufactured by Nippon Polyurethane Industry Co., Ltd.) as an isocyanate crosslinking agent and 0.1 parts of a silane coupling agent (product name: KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.) were added to prepare a pressure-sensitive adhesive composition (solution). The obtained adhesive composition solution was applied onto a 38 μm thick separator (a polyethylene terephthalate film with a release-treated surface) so that the thickness after drying would be 12 μm, and the layer was dried at 100° C. for 3 minutes to remove the solvent, obtaining an adhesive layer. Then, the layer was heated at 50° C. for 48 hours to carry out a crosslinking treatment. Hereinafter, this adhesive layer will be referred to as the "image display section side adhesive layer (B-1)".
[0131] Production Example 4 (Production of Pressure-Sensitive Adhesive Layer (B-2) on Image Display Side) The adhesive composition solution obtained in Production Example 3 was applied onto a 38 μm thick separator (a polyethylene terephthalate film with a release-treated surface) so that the thickness after drying would be 15 μm, and the layer was dried at 100° C. for 3 minutes to remove the solvent, obtaining an adhesive layer. Thereafter, the layer was heated at 50° C. for 48 hours to carry out a crosslinking treatment. Hereinafter, this adhesive layer will be referred to as the "image display section side adhesive layer (B-2)".
[0132] Example 1 (Production of adhesive composition with ultraviolet absorbing function) To the obtained acrylic adhesive composition (a-1), 1.4 parts of 2,4-bis-[{4-(4-ethylhexyloxy)-4-hydroxy}-phenyl]-6-(4-methoxyphenyl)-1,3,5-triazine (trade name: Tinosorb S, manufactured by BASF Japan) dissolved in butyl acrylate to a solid content of 15% and 0.2 parts of bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (trade name: Irgacure 819, having absorption resistance in the wavelength range of 200 to 450 nm, manufactured by BASF Japan) were added and stirred to obtain an adhesive composition with ultraviolet absorbing function.
[0133] The pressure-sensitive adhesive composition with ultraviolet absorbing function was applied onto a release-treated film of a release film so that the thickness of the pressure-sensitive adhesive layer after formation was 150 μm, and then a release film was attached to the surface of the pressure-sensitive adhesive composition layer. Thereafter, illuminance: 6.5 mW / cm 2 , Light amount: 1500mJ / cm 2The pressure-sensitive adhesive composition layer was photocured under the above conditions to form a viewing-side pressure-sensitive adhesive layer (A-1).
[0134] (Production of polarizing film (P-1)) A 25 μm-thick triacetyl cellulose film was attached to the viewing side of a polarizer made of a 12 μm-thick stretched polyvinyl alcohol film impregnated with iodine using a polyvinyl alcohol-based adhesive, and a 20 μm-thick acrylic film was laminated to the image display surface of the polarizer using a polyvinyl alcohol-based adhesive to obtain a polarizing film (P-1). The polarization degree of the polarizing film was 99.995.
[0135] (Manufacturing of polarizing film with adhesive layer) A viewing-side adhesive layer (A-1) was laminated on the viewing side of the polarizing film (P-1) (i.e., the surface of a 25 μm-thick triacetyl cellulose film). An image display section side adhesive layer (B-1) was laminated on the image display section side surface of the polarizing film (P-1) (i.e., the surface of an acrylic film with a thickness of 20 μm), and a retardation film (thickness: 56 μm, material: polycarbonate) and an image display section side adhesive layer (B-2) were further laminated to form a polarizing film with an adhesive layer. The obtained polarizing film with an adhesive layer had a configuration of viewing-side adhesive layer (A-1) / polarizing film (P-1) / image display section side adhesive layer (B-1) / retardation film / image display section side adhesive layer (B-2).
[0136] Examples 2 to 10 A polarizing film with a pressure-sensitive adhesive layer was formed in the same manner as in Example 1, except that the amount of ultraviolet absorber added and the thickness of the pressure-sensitive adhesive layer on the viewing side after formation were as shown in Table 1.
[0137] Examples 11 to 13 A polarizing film with a pressure-sensitive adhesive layer was formed in the same manner as in Examples 1 to 3, except that the retardation film and the pressure-sensitive adhesive layer (B-2) on the image display portion side were not formed.
[0138] Comparative Examples 1 to 4 A polarizing film with a pressure-sensitive adhesive layer was formed in the same manner as in Examples 11 and 1, except that the type of polarizing film used was as shown in Table 1 and the pressure-sensitive adhesive layer on the viewing side was not formed. The polarizing film (P-2) was as follows.
[0139] (Production of polarizing film (P-2)) A 60 μm-thick triacetyl cellulose film was attached to the viewing side of a polarizer made of a 12 μm-thick stretched polyvinyl alcohol film impregnated with iodine using a polyvinyl alcohol-based adhesive, and a 40 μm-thick triacetyl cellulose film was laminated to the image display side surface of the polarizer using a polyvinyl alcohol-based adhesive to obtain a polarizing film (P-2). The polarization degree of the polarizing film was 99.995.
[0140] Comparative Examples 5 to 8 A polarizing film with a pressure-sensitive adhesive layer was formed in the same manner as in Examples 11 and 1, except that the type of acrylic pressure-sensitive adhesive composition forming the visible-side pressure-sensitive adhesive layer and the amount of UV absorber added were as shown in Table 1.
[0141] The obtained pressure-sensitive adhesive layer and the polarizing film with the pressure-sensitive adhesive layer were evaluated as follows.
[0142] <Polymerization rate> The release film of the visible-side adhesive layer used in the examples and comparative examples was peeled off, and only the visible-side adhesive layer was placed on a weighed aluminum petri dish. The weight of (aluminum petri dish + visible-side adhesive layer) was measured to determine the weight of the adhesive layer before drying. After drying at 130°C for 2 hours and cooling at room temperature for about 20 minutes, the weight of (aluminum petri dish + adhesive) was measured again to determine the weight of the visible-side adhesive layer after drying. The polymerization rate was calculated using the following formula.
number
[0143] <Gel fraction> About 0.1 g was taken from the visible-side pressure-sensitive adhesive layer used in the examples and comparative examples, wrapped in a porous tetrafluoroethylene sheet (trade name: NTF1122, manufactured by Nitto Denko Corporation) with an average pore size of 0.2 μm, and then tied with a kite string. The weight at that time was measured (Zg), and this weight was taken as the weight before immersion. The weight before immersion was the total weight of the visible-side pressure-sensitive adhesive layer (the pressure-sensitive adhesive layer collected above), the tetrafluoroethylene sheet, and the kite string. The total weight of the tetrafluoroethylene sheet and the kite string was also measured (Yg). Next, the visible-side pressure-sensitive adhesive layer wrapped in the tetrafluoroethylene sheet and tied with the kite string (referred to as "sample") was placed in a 50 mL container filled with ethyl acetate and left to stand at 23° C. for 7 days. The sample (after ethyl acetate treatment) was then removed from the container, transferred to an aluminum cup, and dried in a dryer at 130°C for 2 hours to remove the ethyl acetate, after which the weight was measured (Xg), and this weight was taken as the weight after immersion. The gel fraction was calculated from the following formula. Gel fraction (wt%)=(XY) / (ZY)×100
[0144] <Measurement of transmittance and b* value of visible side adhesive layer> The release film of the visible side adhesive layer used in the examples and comparative examples was peeled off, and the visible side adhesive layer was attached to a measuring jig and measured with a spectrophotometer (product name: U4100, manufactured by Hitachi High-Technologies Corporation).
[0145] <Residual stress> A test piece was prepared by cutting out a piece of 30 mm wide and 50 mm long from the visible side pressure-sensitive adhesive layer used in the examples and comparative examples, and forming it into a cylindrical shape. This was placed with a chuck gap of 20 mm, and the test piece was pulled 60 mm (300%) at a pulling speed of 200 mm / min (the chuck gap after pulling was 80 mm). The test piece was fixed (held) at the position where it was pulled 60 mm for 300 seconds, and the stress value (N) after 300 seconds was measured. The residual stress was calculated using the following formula. Residual stress after 300 seconds = stress value after 300 seconds (N) / (4 x thickness of test piece / 10)
[0146] <Optical reliability> Both sides of the polarizing film with the adhesive layer obtained in the examples and comparative examples were laminated with glass (product name: S200200, thickness: 1.3 mm, size: 45 mm x 50 mm, manufactured by Matsunami Glass Industry Co., Ltd.), and then autoclaved for 15 minutes (atmospheric pressure: 0.5 MPa, temperature: 50°C). For comparative examples 1 to 4, the adhesive layer on the image display unit side of the polarizing film or retardation film side was laminated with the above glass, and the same autoclaving was performed as above. Thereafter, the film was placed under the following various reliability conditions, and the transmittance was measured with an ultraviolet-visible-near infrared spectrophotometer (product name: V7100, manufactured by JASCO Corporation). The amount of change in transmittance from the initial value was determined. Evaluation was performed according to the following evaluation criteria. (Various reliability conditions) (Condition 1) 85℃×500h (Condition 2) 60℃, 95% x 500h (Condition 3) Heat shock (HS) (-40℃ to 85℃) x 300 cycles (Condition 4) Under UV irradiation × 100h, illuminance: 500W / cm 2 (300~700nm), Environmental temperature: 60~65℃, Environmental humidity: 50% (Evaluation Criteria) ◯: The change in transmittance is 2.0% or less. △: The amount of change in transmittance exceeds 2.0% and is 3.0% or less. ×: The change in transmittance exceeds 3.0%.
[0147] <Glue stains, dimensional accuracy, edge appearance> The polarizing film with the adhesive layer obtained in the examples and comparative examples was cut into a size of 25 mm x 30 mm using a super cutter. Then, the four sides of the cut pieces were cut off by 0.05 mm using an edge processing machine (Megalo Technica Co., Ltd.) to obtain samples. The sides of the samples were visually inspected for glue stains to confirm the presence or absence of glue stains. The dimensional accuracy and edge appearance were observed using an optical microscope and evaluated according to the following evaluation criteria. (Dimensional accuracy) ○:Within ±0.3mm ×: Exceeds ±0.3 mm (Exterior view of end) ○: When the edge is not sticky when touched with the hand ×: If the edge is sticky when touched with your hand
[0148] [Table 1]
[0149] In Table 1, P-1 represents the polarizing film (P-1), P-2 represents the polarizing film (P-2), a-1 represents the acrylic pressure-sensitive adhesive composition (a-1) obtained in Production Example 1, a-2 represents the acrylic pressure-sensitive adhesive composition (a-2) obtained in Production Example 2, B-1 represents the pressure-sensitive adhesive layer (B-1) on the image display portion obtained in Production Example 3, and B-2 represents the pressure-sensitive adhesive layer (B-2) on the image display portion obtained in Production Example 4. (B-2) is shown. [Explanation of symbols]
[0150] 1. Polarizing film with adhesive layer 2a Visible side adhesive layer 2b Adhesive layer on image display side 3a Transparent protective film on the viewing side 3b Transparent protective film on image display side 4 Polarizer 5. Polarizing Film 6 Cover glass or cover plastic 7 Liquid crystal display (LCD) or organic light emitting diode (OLED) 8a, 8b Adhesive layer 9 Sensor Layer
Claims
1. A polarizing film with a pressure-sensitive adhesive layer for use on a viewing side of an image display unit in an image display device, The polarizing film with a pressure-sensitive adhesive layer has a polarizing film and pressure-sensitive adhesive layers on both sides of the polarizing film, The polarizing film has a polarizer and transparent protective films on both sides of the polarizer, The transparent protective film on the viewing side of the polarizer has a transmittance at a wavelength of 380 nm of 6% or more and 30% or less, the transparent protective film on the viewing side of the polarizer is at least one film selected from the group consisting of a triacetyl cellulose film, an acrylic film, a polyethylene terephthalate film, and a polyolefin film having a cyclo- or norbornene structure, and has a thickness of 30 μm or less; The transparent protective film on the image display portion side of the polarizer has a thickness of 1 to 20 μm, and the pressure-sensitive adhesive layer on the viewing side of the polarizing film has an ultraviolet absorbing function, The pressure-sensitive adhesive layer on the viewing side of the polarizing film has a gel fraction of 75% or more and 89% or less, the pressure-sensitive adhesive layer on the viewing side of the polarizing film contains an ultraviolet absorber, the ultraviolet absorber being a triazine-based ultraviolet absorber, a benzophenone-based ultraviolet absorber, an oxybenzophenone-based ultraviolet absorber, a salicylic acid ester-based ultraviolet absorber, a cyanoacrylate-based ultraviolet absorber, or a combination of two or more of these; A polarizing film with a pressure-sensitive adhesive layer, wherein none of the transparent protective films on both sides of the polarizer contains an acryloyl-based compound represented by the following general formula (1): 【Chemistry 1】 (In the formula, R 11 represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and R 12 and R 13 each independently represent an alkyl group having 1 to 8 carbon atoms.)
2. 2. The polarizing film with an adhesive layer according to claim 1, wherein the thickness of the adhesive layer on the viewing side of the polarizing film is at least twice the thickness of the adhesive layer on the image display side of the polarizing film.
3. 3. The polarizing film with an adhesive layer according to claim 1, wherein the adhesive layer on the viewing side of the polarizing film has a transmittance of 40% or less at a wavelength of 380 nm and a transmittance of 30% or more at a wavelength of 400 nm.
4. 4. The polarizing film with a pressure-sensitive adhesive layer according to claim 1, wherein the b* value of the pressure-sensitive adhesive layer on the viewing side of the polarizing film is 3.0 or less.
5. 5. The polarizing film with a pressure-sensitive adhesive layer according to claim 1, wherein the pressure-sensitive adhesive layer on the viewing side of the polarizing film contains an acrylic polymer as a base polymer.
6. 6. The pressure-sensitive adhesive layer-attached polarizing film according to claim 1, which is used in a liquid crystal display device or an organic EL display device.
7. 7. An image display device, comprising the pressure-sensitive adhesive layer-attached polarizing film according to claim 1 on a viewing side of an image display section.
8. The polarizing film with a pressure-sensitive adhesive layer according to any one of claims 1 to 6, characterized in that the pressure-sensitive adhesive layer on the viewing side of the polarizing film is formed from an ultraviolet polymer of an ultraviolet-curable acrylic pressure-sensitive adhesive composition containing a monomer component containing alkyl (meth)acrylate and / or a partial polymer of the monomer component, an ultraviolet absorber, and a photopolymerization initiator (A) having an absorption band at a wavelength of 400 nm or more.
Citation Information
Patent Citations
Uv-curing type adhesive composition and its adhesive sheets
JP2001240842A
Polarizing plate and liquid crystal display element
JP2005010329A
Polarizer and liquid crystal display device
JP2008249901A
Ultraviolet curing adhesive composition
JP2009114382A
Anti-reflection film having UV absorption, and manufacturing method thereof
JP2009128770A